A laboratory and filed evaluation of Cold Recycled Mixture for base layer entirely made with Reclaimed Asphalt Pavement. (1st May 2017) - Sangiorgi, Cesare; Tataranni, Piergiorgio; Simone, Andrea; Vignali, Valeria; Lantieri, Claudio; Dondi, Giulio
Highlights: Main research goal: use of 100% RAP for Cold Recycled Mixture base layers. Laboratory and trial field comparison between Cold Recycled Mixture and Hot Mix Asphalt. The presence of 100% RAP does not seem to worsen the compactability of the bituminous mixture. ITS and ITSM test results confirmed the difference in terms of resistance and stiffness between CRM and HMA. The mechanical and physical properties of CRM are strictly related to the mix design and to the quality of RAP. Abstract: Asphalt concrete (AC) recycling is probably the most cost-effective technique for the rehabilitation of stressed road pavements and for the construction of new ones. The increased interest in this technology comes from the need of reducing the costs connected to the production processes and to the use of virgin raw materials. In fact, the benefits connected to the use of Reclaimed Asphalt Pavement (RAP) are related to the possibility of substituting the natural aggregates and the virgin binder of an AC mixture, without negatively affecting its mechanical properties. When this process is made at ambient temperature (Cold Recycled Mixes – CRM), more advantages are brought about with, above all, the reduction in energy consumption and emissions during in plant production and laying, in addition to the actual possibility of achieving durable pavement layers. A CRM totally made of RAP is proposed in this research, the main goal of which was to evaluate the different physical and mechanical characteristics derived by the large use of recycled materials. According to the final mix-design, CRM does not show significant differences in terms of physical properties, when compared to a Hot Mix Asphalt (HMA) for base layers. Moreover, even if the experimental mixture shows lower mechanical values, these are acceptable and higher than the limits imposed by the most common Italian technical specifications for Cold Mix Asphalts containing up to 30% RAP.